2013
DOI: 10.5539/ijps.v5n1p139
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness and Working Memory in Arabic-Speaking Egyptian Preschool Children at Risk for Dyslexia

Abstract: This purpose of this study was to examine the relationship between phonological awareness, verbal working memory, and risk for dyslexia in Arabic language in preschool children. The participants of this study were preschool children between the ages of five and six, who represented two groups: (20) children at risk for dyslexia and (20) children normal without any risk for dyslexia. These children were randomly selected from a larger sample of 425 preschool children in Egypt. Phonological awareness and verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 82 publications
(57 reference statements)
1
5
1
3
Order By: Relevance
“…Results of the current study show that there is no correlation between some phonological processes (Syllables &Sound Deletion Test, Non-Word Repetition Test, and Non-Word Reading Accuracy Test) and the working memory tasks. This also contradicts with the study conducted by Zayed et al, (2013) which indicated the presence of a strong relationship between phonological awareness and working memory that may have an effect on children's phonological sensitivity and reading skills. In addition, the current study results contradict with results reached in a study of Milwidsky (2008) that revealed a close relationship between working memory and phonological awareness.…”
Section: Significance Of Differences Between Males and Females In Worcontrasting
confidence: 53%
See 3 more Smart Citations
“…Results of the current study show that there is no correlation between some phonological processes (Syllables &Sound Deletion Test, Non-Word Repetition Test, and Non-Word Reading Accuracy Test) and the working memory tasks. This also contradicts with the study conducted by Zayed et al, (2013) which indicated the presence of a strong relationship between phonological awareness and working memory that may have an effect on children's phonological sensitivity and reading skills. In addition, the current study results contradict with results reached in a study of Milwidsky (2008) that revealed a close relationship between working memory and phonological awareness.…”
Section: Significance Of Differences Between Males and Females In Worcontrasting
confidence: 53%
“…Phonological awareness has been found to be related strongly with dyslexia among Arabic-speakers (Al Mannai & Everett, 2005;Ashour, 2011;Othman, 2009;Zayed, 2013). It is also evident that intervention is a successful remediation for the reading disorder (Ashour, 2011).…”
Section: Phonological Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…En el caso terapéutico, el diagnóstico y abordaje a menudo le corresponden al terapeuta del lenguaje. Un ejemplo de ello es demostrado por Zayed et al (2013), en el que el fonoaudiólogo es el encargado de la aplicación de pruebas (previa autorización en todas las instancias). En este caso específico, con una serie de tareas fonológicas (discriminación fonológica, articulación, identificación de rimas, sonido inicial y reconocimiento fonema-grafema), la conclusión determinó que los niños en riesgo de presentar dislexia mostraban dificultades acentuadas en la identificación de rimas; en otros casos, el abordaje terapéutico de la conciencia fonológica ha sido estudiado a la luz de las implicaciones reales del trabajo sobre esta área comparando los efectos de la intervención en niños con trastornos fonológicos y niños con normodesarrollo del habla y del lenguaje que denota una mejoría en este aspecto.…”
Section: Universidad De La Sabana | Facultad De Educaciónunclassified